eCM 2015
DOI: 10.22203/ecm.v029a19
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an in vitro 3D bone culture model with perfused and mechanically stressed ceramic scaffold

Abstract: An engineered three dimensional (3D) in vitro cell culture system was designed with the goal of inducing and controlling in vitro osteogenesis in a reproducible manner under conditions more similar to the in vivo bone microenvironment than traditional two-dimensional (2D) models. This bioreactor allows efficient mechanical loading and perfusion of an original cubic calcium phosphate bioceramic of highly controlled composition and structure. This bioceramic comprises an internal portion containing homogeneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 64 publications
0
30
0
Order By: Relevance
“…No doubt, considering the short history for FMOD reprogramming investigation, many more studies are warranted to enrich our knowledge about FReP cells to the levels that we understand currently available stem cells, including further clarifying the FMOD reprogramming mechanism, and revealing the potential immune-modulation and paracrine function of FReP cells. Additionally, more extensive investigation will be required to translate FReP cell investigation from bench characterization to clinical application, including, but not limited to, optimizing the cell seeding density and culture procedure [8386], minimizing the xenogeneic exposure for in vitro osteogenic initiation, enhancing the properties of the supporting osteoconductive scaffold(s), improving the interaction between FReP cells and scaffolds [85, 86], and large animal efficacy and safety tests.…”
Section: Discussionmentioning
confidence: 99%
“…No doubt, considering the short history for FMOD reprogramming investigation, many more studies are warranted to enrich our knowledge about FReP cells to the levels that we understand currently available stem cells, including further clarifying the FMOD reprogramming mechanism, and revealing the potential immune-modulation and paracrine function of FReP cells. Additionally, more extensive investigation will be required to translate FReP cell investigation from bench characterization to clinical application, including, but not limited to, optimizing the cell seeding density and culture procedure [8386], minimizing the xenogeneic exposure for in vitro osteogenic initiation, enhancing the properties of the supporting osteoconductive scaffold(s), improving the interaction between FReP cells and scaffolds [85, 86], and large animal efficacy and safety tests.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous cyclic loading studies have focused on loading parameters (strains ranging from 1 to 10%) that are much different from the physiological range . Furthermore, the substrate on which the cells are attached should replicate mechanical properties of native osteoinductive environment of the tissues to extract appropriate physiological response …”
Section: Introductionmentioning
confidence: 99%
“…On the whole, the flowrate value remains a confounding variable scattered across four orders of magnitude (from 2 µl/min; Bouet, Cruel, et al, to 60 ml/min; Chen et al, ) without clear patterns between the selected flowrate and observed osteogenic effects. Selected flowrates in perfusion studies do not necessarily rely on experimental design and are often seemingly arbitrarily fixed to 0.1 or 1 ml/min (Allori et al, ; Gardel et al, ; Gomes et al, ; Holtorf, Datta, Jansen, & Mikos, ; Jaasma & O'Brien, ; Sinlapabodin, Amornsudthiwat, Damrongsakkul, & Kanokpanont, ; Van Gordon et al, ) or refer to different setups.…”
Section: Flow Effectsmentioning
confidence: 99%
“…Another popular stimulation methodology is to submit cells to the dual effect of perfusion and cyclic mechanical loading of the scaffold; submitting cells to both flow‐induced shear stresses and substrate deformation is an attempt to better reproduce in vivo stimuli (Bouet, Cruel, et al, ; David et al, ; Dumas et al, ; Stops, Heraty, Browne, O'Brien, & McHugh, ; Zong ming et al, ). Nonetheless, to our best knowledge, fluid movement due to substrate deformation has never been quantified, making the resulting cell responses much more arduous to interpret as the flow patterns remain unknown.…”
Section: Obstacles In Defining Optimal Flow Effectsmentioning
confidence: 99%